PEMAHAMAN RASIONAL PEMBIAYAAN SYARIAH, RELEGIUSITAS, PRIMORDIALISME PENGUSAHA DAN PENGARUHNYA TERHADAP SIKAP PENGUSAHA DALAM MEMILIH PEMBIAYAAN DI BANK SYARIAH - Wibowo, R. Ery; Hardiwinoto, Hardiwinoto (Benefit: Jurnal Manajemen dan Bisnis, 2015)
This study provides empirical evidence of a rational understanding of  sharia finance, relegiusitas, primordialism and influence on the attitudes of entrepreneurs in selecting the financing in Islamic banks. Sources of data drawn from the population of Muslims in the city of Semarang entrepreneurs who are members of the organization ICMI (Association of Indonesian Muslim Scholar) Semarang, amounting to 46 entrepreneurs.With the number of samples taken by 35 entrepreneur. The questionnaire was distributed in August 2014. The results also show the R square of 0.643. With the results of hypothesis testing that proves that the attitude of entrepreneur in selecting the financing in Islamic banks more directly influenced by rational understanding of Islamic finance with the level of  sig. at 0,00. The conclusion of this study is that the attitude of entrepreneur  in choosing financing in shariabanks more directly influenced by rational factors. Understanding the underlying profit  factors of business entrepreneurs in choosing financing in Islamic banks. While relegiusitas factors and primordial or organization is not evident similarity ties directly influence the attitude of entrepreneurs in choosing financing in shariabanks.